2017
DOI: 10.24905/jip.v2i2.726
|View full text |Cite
|
Sign up to set email alerts
|

Strategi Pengelolaan Sumber Daya Alam Desa Ponggok

Abstract: Abstrak

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…The findings above are in line with several studies on community service that have been conducted, such as research conducted by [10] and [1] find the local economic potential based on local wisdom is one of the keys to the success of community service in the village of Ponggok Klaten Central Java. In addition, other research conducted by [11] also found that youth participation was accompanied by community involvement being one of the keys to the success of Bumdes Tirta Mandiri in Umbul ponggok.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The findings above are in line with several studies on community service that have been conducted, such as research conducted by [10] and [1] find the local economic potential based on local wisdom is one of the keys to the success of community service in the village of Ponggok Klaten Central Java. In addition, other research conducted by [11] also found that youth participation was accompanied by community involvement being one of the keys to the success of Bumdes Tirta Mandiri in Umbul ponggok.…”
Section: Resultssupporting
confidence: 88%
“…According to the Council of Microfinance Equity Funds (2012) governance is a system that can keep the organization in the main corridor, which has the function of 1) setting goals, organizational mission and implementation, 2) determining the strategic direction of the organization, 3) maintaining organizational health and minimizing risk, 4) ensuring organizational accountability, 5) ensuring the organization has sufficient resources for the organization to run. While [1] mentions governance is effective decision making, built on the basis of organizational culture, values, systems, various processes, policies and organizational structure, aims to achieve profitable, efficient and effective business in managing risk and being responsible for stakeholder.…”
Section: Literature Reviewmentioning
confidence: 99%
“…https://pddi.kemendesa.go.id/ (Sumber Data: PODES 2018 -BPS), diakses pada 25 Agustus 2020 2 UmmiZakiyah, et al, 2017, Strategi Pengelolaan Sumber Daya Alam Desa Ponggok, Jurnal Ilmu Pemerintahan. Vol 2, No.…”
unclassified